RESEARCH OF INFLUENCE OF THE RODS CONSTRUCTION ON THEIR COOLING ABILITY AT FROSTING OF SILUMINS BY METHOD OF NUMERICAL MODELING - V. Yu. Stetsenko; R. V. Konovalov; K. N. Baranov (Литьë и металлургия, 2012)
Numerical modeling of heat transfer coefficient on the surface of the water-cooled rod with a slotted and jet cooling was made.  calculations were carried out in a free, open  source  CFD software package OpenFOAM. it is shown that jet cooling is more uniform and intense compared to the slotted cooling.